Efecto de inductores de resistencia sobre enfermedades foliares en maíz (Zea mays L.) durante la época seca - Loor Solórzano, Jackson Benito (2025)
The present research was conducted at the Escuela Superior Politécnica de Manabí, Manuel Félix López (ESPAM-MFL), with the objective of determining the effectiveness of resistance inducers against foliar diseases and in the productivity of maize cultivation. For the analysis of productive and sanitary variables, analysis of variance (ANOVA) and the Tukey test (P<0.05) were used, including sources of variation with statistical significance. The INFOSTAT software was used for data analysis. The five treatments under study were: T1: Acetylsalicylic acid; T2: Salicylic acid; T3: Calcium phosphate; T4: Potassium phosphate; and T5: Control, with T3 being Calcium phosphate. The results showed that the application of resistance inducers in maize cultivation did not affect the incidence of viral and Bipolaris-related sanitary problems in the study area, and the application of these inducers did not influence agronomic and production variables, although slight effects were observed with the application of resistance inducers.